IDENTITY AND BODY BORDERS: THE PERCEPTION OF THE KENYA SOMALIA BORDER - Behr, Agnes Wanjiru (American Journal of International Relations, 2018)
Purpose: The study sought to understand how the identity of the ethnic Somalis and the geographic settings inform the perception of the Kenya-Somalia border. Methodology: The research took a poststructuralist approach via qualitative methodology where information was derived from five focus groups, key informants and one on one interviews from Garissa and Mandera Counties in the period of 2016-2017. Besides, observations, field experiences, films, and documentaries helped to triangulate the findings for validity purposes. Additionally, historiography was employed through archival materials from the Kenya National Archives. Result: The study shows that body borders elasticizes the Kenya-Somalia border and makes it spatial. Second, ethnic Somalis elastic view of the border through the body is a means of survival but gives the perception to the Kenyan government that the border community does not recognize the international border. Furthermore, the pastoral-nomadic norms of the ethnic Somalis shows elastic view of the Kenya-Somalia border due to the arid to semi-arid territory which calls for negotiated living spaces as opposed to the static view of the same by Kenyan governments. The unique contribution to the theory, practice and policy: Cognitive psychology, Constructivism and discourse analysis used together shows a pattern derived from everyday discourse and behaviors that shape the thinking on border studies. Language goes beyond verbal communication to a psychological tap that shows the behavior of a community as informed by fears and the need to alleviate the fears. The behaviors shape the norms, and therefore, constructivism displays state behaviors and actions or inaction. Also, transfer of the social-cultural to the state norms shows a divide in border thinking where two or more identities come together. The issue should, therefore, be how to alleviate the fears both current and historical from both the state and ethnic Somalis instead of looking at each as the threat to the other.